Blurring the Boundaries Between Life and Death: - Daisy Richards (Exchanges, 2018)
This article aims to engage with and problematise traditional ideas relating to re-enacted sequences within documentary films, and how these sequences might allow audiences a new and previously denied access to some level of so-called ‘truth.’ Positing that re-enactments essentially function as devices of distraction and fantasy, Bill Nichols (2008) sheds invaluable insight onto the nature of ‘truth’ in the use of re-enactments in documentary filmmaking. This article engages with, and attempts to build upon this existing scholarship, by performing a closer examination of the ways in which filmmakers deploy strategies of re-enactment in Carol Morley’s Dreams of a Life (2011) and Clio Barnard’s The Arbor (2010). Re-enactments are employed by their respective filmmakers not solely in order to present complete rejections of reality, but also to depict the filmmaking processes and the ways in which they have been ‘worked through’ to audiences in innovative and reflexive ways. Through the specific utilisation of stylistic features that directly and obtrusively call attention to a documentary’s status as documentary, filmmakers do not wholeheartedly reject real-life events. Instead, they continually draw attention to the artifice of their artworks, reminding audiences that there can, indeed, only ever be ‘a view from which the past yields up its truth’, and that these views are completely and wholly unstable and elusive.